Factors in the choice of exchange rate regime with special reference to the Caribbean - Blackman, Sir Courtney ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Reviews the CARICOM experience with various exchange rate regimes over the past three decades. Pays special attention to foreign exchange markets in conditions of chronic disequilibrium, and to the role of the cambio system. Develops a normative framework for the choice of a feasible exchange rate regime for a given country.